A Feasibility Study on Spicy Malunggay Brownies at Susano Road, Novaliches, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The researcher chose spicy malunggay brownies as the main product of their business. A brownie is a type of dessert like cake but it does not include a leavener on it and that what makes the brownie different from cake. They chose to have this product because they know that Filipino loves to eat dessert that’s why they chose brownie since brownie is one of the desserts that is known in the world not only in the Philippines. They added malunggay leaves in it but in powder form and chili powder to improve the taste of the brownie. Those two ingredients that was added has a different benefits, it can gives us energy, nutrition, it can also help in formation of red blood cells and many more benefits.The method that the researcher chose was survey questionnaire method. Survey questionnaire method is a method which the researchers gave out questionnaires to be answered by the chosen respondents. The questionnaire contains questions that are needed in the study. After the study has conducted, it shows that the business of sweet and spicy brownie delights is feasible the researchers conducted a survey and based on the data or answers that they had gathered to their chosen respondents, they found that their product is feasible or accepted on the market and business industry. All of the respondents of this study agreed that it will be acceptable to the people and market.On this study, the researchers focus and studied the feasibility of spicy malunggay brownies. They put all the information and data that was needed in this study. They showed here how they come up with that business and how they end up with that product. The researcher also put here in this study how they made that product and all the benefit that their product has they also offer other products but still has malunggay and brownies in it on this research, the researchers seek to find the number of acceptance of their product. To know if this study is feasible, the researchers conducted a survey which is called survey questionnaire method this survey has a questionnaire that contains a questions that they needed in their study the researcher handed out the questionnaires to individual after thery conducted the survey they interpreted the data that they had gathered after they interpreted the data they found that the study of spicy malunggay brownies is feasible on the possible customers.
Keywords: spicy malungay brownies, feasibility study, BCP